Introducing the FSNet-Africa model: Strengthening African capacity to tackle Africa’s wicked development challenges - Mkandawire, Elizabeth; Mentz-Coetzee, Melody; Swanepoel, Frans (New Agenda: SA Journal of Social and Economic Policy, 2024)
The challenges inherent in the Sustainable Development Goals (SDGs) are interconnected and complex (United Nations, 2018). Overcoming these challenges requires adopting solutions that transcend conventional silo approaches and actively promote inclusivity (El-Jardali et al., 2018). However, these approaches are not the norm, and deliberate efforts are needed to disrupt traditional approaches to development. Research activities also need to adapt so that they are underpinned by capacity development, knowledge management, and partnerships of co-production, communication and coordination (Lamptey et al., 2024).